ANALISIS PENGARUH PENYAJIAN LAPORAN KEUANGAN, KAPASITAS SDM, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN - Maulina Ardiani; Nunung Aini Rahmah (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of financial statement presentation, human resource capacity, and information technology utilization on the quality of financial statements at the Department of Community and Village Empowerment of West Java Province. The research uses a quantitative approach with explanatory methods. Data were collected through questionnaires distributed to employees involved in financial reporting processes and analyzed using the SPSS software for multiple linear regression. The results indicate that presenting financial statements based on Government Accounting Standards (PSAP 01) has a positive and significant impact on the quality of financial statements. Meanwhile, human resource capacity and the utilization of information technology do not have a significant effect on financial statement quality. However, simultaneously, the three variables have a significant influence on the quality of financial statements. These findings suggest that compliance with PSAP 01 plays a crucial role in enhancing report quality, while improvements in HR capacity and IT systems require further optimization to effectively contribute to financial reporting quality. Keywords : Financial statement presentation, human resource capacity, information technology, financial statement quality, government accounting